2007
DOI: 10.1111/j.1365-2133.2007.08329.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitizing activity of hypericin and hypericin acetate after topical application on normal mouse skin

Abstract: Our results indicate that hypericin is an effective photosensitizer not only after systemic administration, but also after topical application, especially when applied as its precursor acetate ester. Moreover, our data provide some insights on safety limits and the time course of skin phototoxicity following hypericin and hypericin acetate application. These data will aid in developing protocols for future photodynamic therapy in the dermatological clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…These results are consistent with previous studies of penetration and distribution of hypericin in mice, where after application on the skin, hypericin penetrated after 4 h and was retained mainly in the stratum corneum (44). A previous study showed that the passage of hypericin into the circulatory system is minimal, with undetectable levels in plasma or serum (45). Retention of hypericin in the skin guarantees a treatment that targets the affected area, thus avoiding possible systemic toxic effects, as happens with other drugs used for the treatment of CL or even with other photosensitizers used to treat other diseases (46,47).…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with previous studies of penetration and distribution of hypericin in mice, where after application on the skin, hypericin penetrated after 4 h and was retained mainly in the stratum corneum (44). A previous study showed that the passage of hypericin into the circulatory system is minimal, with undetectable levels in plasma or serum (45). Retention of hypericin in the skin guarantees a treatment that targets the affected area, thus avoiding possible systemic toxic effects, as happens with other drugs used for the treatment of CL or even with other photosensitizers used to treat other diseases (46,47).…”
Section: Discussionsupporting
confidence: 82%
“…Phototoxic reactions mainly occur in the skin and eyes; thus, dermal and ocular exposure to compounds can be a predictive factor for in vivo phototoxicity as well as systemic exposure (Boiy et al, 2008;Seto et al, 2009). PK characterizations of compounds were conducted with a focus on plasma, skin, and eyes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, FA might be a major contributor to FFinduced phototoxicity after metabolism of FF. For photosafety assessments, exposure of compounds and their retention to dermal/ocular tissues can also be a key consideration because phototoxic reactions typically occur in the skin and eyes (Boiy et al, 2008;Seto et al, 2009). Therefore, in this study, the PK behavior of FF and its metabolites was assessed with a focus on plasma and skin/eyes in rats after oral administration of FF.…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentration gap of hypericin affinities in the micromolar range for binding these receptors and nanomolar plasma concentrations measured in humans after intake of therapeutic doses made it unlikely to account for the antidepressive principle (Staffeldt et al 1994;Kerb et al 1996;Brockm€ oller et al 1997). Phototoxicity is a feature attracting attention to hypericin (Boiy et al 2008;Davids et al 2008), being currently under investigation regarding its antimetastatic and antiangiogenic properties in the treatment of glioblastomas or melanoma (Davids et al 2008;Barliya et al 2011;Dror et al 2013). The flavonoids, biapigenine, hyperoside, and isoquercitrin, showed moderate antidepressive activity in the forced swim test, a behavioral animal model for depression (N€ oldner and Sch€ otz 2002;Paulke et al 2008) with yet unknown mechanism.…”
Section: Introductionmentioning
confidence: 97%